Vertical cloud distribution in the Uranian atmosphere - Kostogryz, N.M. (Advances in Astronomy and Space Physics, 2011)
In this work, the vertical cloud distribution in the Uranian atmosphere is investigated. We used the method of determinination of the deviation scope of the real atmosphere from homogeneity conditions. The idea of this methods is that the diffusely reffected radiations form at different effective depths in the atmosphere, namely: the strong absorption bands form higher in the atmosphere than weak ones. The same is for separate absorption bands: their centres form in higher atmospheric layers than other points of bands or lines contours. The relative methane concentration for all points of the contours of absorption bands will be the same only for a homogeneous atmosphere and will show the systematic deviation in the center and near the edge of the absorption bands in the case of an inhomogeneous atmosphere. It was obtained that Uranus' atmosphere has two cloud layers: the first one in the region with pressure within the range 1.5 − 1.8 bar, and the second one in the region with the pressure 3.5 − 5.5 bar. We also can conclude that aerosol was more abundant in 1981 compared to 1993 and 1995 which was found in our previous work.